1988
DOI: 10.1073/pnas.85.5.1677
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic regulation of protein phosphorylation in bovine adrenal chromaffin cells.

Abstract: Chromaffin cells were isolated from bovine adrenal medullae and maintained in primary culture. After prelabeling with 32PO4, exposure of the chromaffm cells to acetylcholine increased the phosphorylation of a Mr -100,000 protein and a Mr =60,000 protein (tyrosine hydroxylase), visualized after separation of total cellular proteins in NaDodSO4/polyacrylamide gels. Immunoprecipitation with antibodies to three known phosphoproteins ("100-kDa," "87-kDa," and protein HI) revealed an acetylcholine-dependent phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Synapsin I1 is a neuron-specific phosphoprotein found in central and peripheral neurons and in the neural crest cell-derived adrenal chromaffin cells. Its phosphorylation state has been shown to parallel closely exocytotic release of catecholamines in BACC following cholinergic stimulation (Haycock et al, 1988). In this study, we show that histaminergic stimulation also shows a good correspondence between synapsin I1 phosphorylation and catecholamine release.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Synapsin I1 is a neuron-specific phosphoprotein found in central and peripheral neurons and in the neural crest cell-derived adrenal chromaffin cells. Its phosphorylation state has been shown to parallel closely exocytotic release of catecholamines in BACC following cholinergic stimulation (Haycock et al, 1988). In this study, we show that histaminergic stimulation also shows a good correspondence between synapsin I1 phosphorylation and catecholamine release.…”
Section: Discussionsupporting
confidence: 65%
“…Accordingly, we first needed to determine the concentrations of histamine and nicotine that produced maximal effects. We have reported previously that doses of nicotine above 5 X 1 0-5 M produce maximal effects on secretion and phosphorylation (Haycock et al, 1988). The dose-response relationships for histamine-stimulated [3H]NE release (not shown) and synapsin I1 phosphorylation (Fig.…”
Section: Additivity Of Histamine and Nicotine Effectsmentioning
confidence: 78%
See 1 more Smart Citation
“…chain elongation. It is phosphorylated on threonine residues by a specific eEF-2 kinase, (previously termed Caa+/calmodulin.dependent protein kinase III [3,4]) and its phosphorylation is increased in intact ceils in response to stimuli which increase intracellular Ca z÷'ion concentrations [6][7][8][9][10][11][12][13]. Phosphorylation of the endogenous eEF-2 impairs the translation of mRNA in the reticulocyte lysate celt-free system [5] and several other lines of evidence show that phosphorylated eEF-2 is inactive, or has only low activity [3,4,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exocytotic phenomenon is well described, the Ca2-dependent signaling events leading to secretion are not fully characterized. Extensive studies have indicated that protein phosphorylations serve as important signaling intermediates (Amy and Kirschner, 1981;Lee and Holz, 1986;Michener et al, 1986;Gutierrez et al, 1988;Haycock et al, 1988;Firestone and Browning, 1992). Although most phosphorylations occur on serine and threonine residues, a role for tyrosine phosphorylation is suggested from the secretagogue-dependent tyrosine phosphorylation of several proteins, the most prominent of which are the mitogen-activated protein kinases (MAPKs) (Dahmer et al, 1990;Ely et al, 1990).…”
mentioning
confidence: 99%